1978
DOI: 10.1002/aja.1001510405
|View full text |Cite
|
Sign up to set email alerts
|

The ultrastructure of the nephrons of the desert rodent (Psammomys obesus) kidney II. Thin limbs of henle of long‐looped nephrons

Abstract: Long nephrons are derived from juxtamedullary glomeruli. In their descent through the outer medulla toward the inner medulla, the thin descending limbs (TDLs) of long loops of H m l e are consistently excluded from the vascular bundles and occupy the interbundle region. The outer medullary segment of long TDLs (Type IZ epithelium) is elaborately developed with numerous cellular interdigitations, microvilli, and a cytoplasm well equipped with numerous organelles.The inner medullary segment of these long TDLs is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

1978
1978
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 28 publications
1
29
0
Order By: Relevance
“…In the final segment, including the loop bend and the ascending thin limb, the epithelial cells deeply interdigitated with each other again. Following TEM studies in the mouse (DIETERICH et al, 1975), desert rodent Psammomys obesus ( BARRETT et al, 1978a, b), and hamster (BACHMANN and KRIZ, 1982) confirmed the findings of SCHWARTZ and VENKATACHALAM (1974), who showed the morphological diversity of the thin limb.…”
supporting
confidence: 63%
“…In the final segment, including the loop bend and the ascending thin limb, the epithelial cells deeply interdigitated with each other again. Following TEM studies in the mouse (DIETERICH et al, 1975), desert rodent Psammomys obesus ( BARRETT et al, 1978a, b), and hamster (BACHMANN and KRIZ, 1982) confirmed the findings of SCHWARTZ and VENKATACHALAM (1974), who showed the morphological diversity of the thin limb.…”
supporting
confidence: 63%
“…The still enigmatic interplay between the medullary vasculature and the segments of Henle's loop, specifically with respect to Hargitay and Kuhn's idea of the countercurrent multiplication principle enunciated in 1951, then stimulated him to study the detailed morphology of the epithelia of the loop of Henle [3,8,9,13,32,59,61,88]. A long-standing collaboration with Jürgen Schnermann began in 1971 and produced two major papers on the topography and heterogeneous width of the loop portions [32,61].…”
Section: The Renal Medulla and Urinary Concentrating Mechanismmentioning
confidence: 99%
“…While there is no evidence for active sodium secretion by the rabbit descending limb in vitro [15], the characteristics of the ultrastructure of the epithelium of the prox imal half of the juxtamedullary descending limb ('type II epithelium') of the Psammo mys [1] suggest that it is capable of active ion transport. Moreover, Majack et al [18] re cently demonstrated the presence of ATPase in type II epithelium but not in other types of epithelium lining the thin loop of Henle of the rat.…”
Section: Sodiummentioning
confidence: 99%
“…In the 6 animals used for cortical micropuncture, the con centration of sodium and potassium in the plasma ultrafiltrate was also determined with the electron probe. 1 Statistical analysis between groups was done using Student's l lest for comparing two independent means [28]. The values reported represent means±SE.…”
Section: Cortical Micropuncturementioning
confidence: 99%